2023
DOI: 10.3389/fcdhc.2023.1095467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on immunity to latent tuberculosis infection

Abstract: Tuberculosis (TB) is an infectious disease that poses a major health threat and is one of the leading causes of death worldwide. Following exposure to Mycobacterium tuberculosis (M.tb) bacilli, hosts who fail to clear M.tb end up in a state of latent tuberculosis infection (LTBI), in which the bacteria are contained but not eliminated. Type 2 diabetes mellitus (DM) is a noncommunicable disease that can weaken host immunity and lead to increased susceptibility to various infectious diseases. Despite numerous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Some studies have suggested that diabetes may increase the risk of acquiring a latent tuberculosis infection, and it might also be associated with an increased risk of progressing from latent tuberculosis to active TB disease. Diabetes could impair immune function, making individuals more susceptible to infections, including tuberculosis [ 24 ]. A systematic review indicated that the cohort study revealed an increased but nonsignificant risk of LTBI among diabetics, but, for the cross-sectional studies, they reached a small and marginally significant relationship between diabetes and LTBI risk [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that diabetes may increase the risk of acquiring a latent tuberculosis infection, and it might also be associated with an increased risk of progressing from latent tuberculosis to active TB disease. Diabetes could impair immune function, making individuals more susceptible to infections, including tuberculosis [ 24 ]. A systematic review indicated that the cohort study revealed an increased but nonsignificant risk of LTBI among diabetics, but, for the cross-sectional studies, they reached a small and marginally significant relationship between diabetes and LTBI risk [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the host's innate immunity and adaptive immunity, this bacteria can remain dormant for decades [3][4][5] . Approximately a quarter of the global population is estimated to be infected, with 5-10% of those infected developing active TB [5][6][7] . According to the Global Tuberculosis Report 2022, China ranks third among countries with a high TB burden.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the host's innate immunity and adaptive immunity, this bacteria can remain dormant for decades [ 4 – 6 ]. Approximately a quarter of the global population is estimated to be infected, with 5% to 10% of those infected developing active TB [ 6 – 8 ]. According to the Global Tuberculosis Report 2022, China ranks third among countries with a high TB burden.…”
Section: Introductionmentioning
confidence: 99%